2021
DOI: 10.1007/s00167-021-06461-7
|View full text |Cite
|
Sign up to set email alerts
|

An older age, a longer duration between injury and surgery, and positive pivot shift test results increase the prevalence of articular cartilage injury during ACL reconstruction in all three compartments of the knee in patients with ACL injuries

Abstract: Purpose To investigate factors that inluence the prevalence of articular cartilage injury in patients with anterior cruciate ligament (ACL) injury. Methods This multicentre study included patients with ACL injury. Logistic regression analysis was conducted to identify factors that inluence the prevalence of cartilage injury during ACL reconstruction. Results A total of 811 patients were enrolled. The factors that signiicantly inluenced the prevalence of cartilage injury were age (odds ratio [OR], 1.04; P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…[6][7][8]30,31 Nakamae et al demonstrated that a longer duration between injury and surgery was significantly associated with an increased prevalence of articular cartilage injury in the medial, lateral, and patellofemoral compartments in older-age patients, and recommended early ACL reconstruction. 30 Brambilla et al reported that the risk of cartilage lesions in the medial compartment increased after a 12-month delay in surgery and that the risk of injury in the lateral femoral condyle was significantly higher in patients who underwent surgery more than 60 months after an ACL injury than in those who underwent surgery within 3 months of injury. 6 In the present study, the duration between injury and surgery was longer in patients aged !40 years than that in patients aged 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8]30,31 Nakamae et al demonstrated that a longer duration between injury and surgery was significantly associated with an increased prevalence of articular cartilage injury in the medial, lateral, and patellofemoral compartments in older-age patients, and recommended early ACL reconstruction. 30 Brambilla et al reported that the risk of cartilage lesions in the medial compartment increased after a 12-month delay in surgery and that the risk of injury in the lateral femoral condyle was significantly higher in patients who underwent surgery more than 60 months after an ACL injury than in those who underwent surgery within 3 months of injury. 6 In the present study, the duration between injury and surgery was longer in patients aged !40 years than that in patients aged 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…age patients, and recommended early ACL reconstruction. 30 Bramblilla et al reported that the risk of cartilage lesions in the medial compartment increased after a 12-month delay in surgery and that the risk of injury in the lateral femoral condyle was significantly higher in patients who underwent surgery more than 60 months after an ACL injury than in those who underwent surgery within three months of injury. 6…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, Choi et al [11] found that FLDs had better stability in pivot shift compared with ALDs, which contradicts the findings of this study. The pivot shift test is important because rotational laxity has been associated with additional surgery required to reduce knee laxity and the development of the early onset of osteoarthritis [19, 32, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared acute and delayed ACL reconstruction in terms of meniscal damage [4, 15, 17, 20, 23, 29, 32], articular cartilage injury [4, 17, 20, 26, 32], functional outcomes [15, 35], subjective outcomes [15, 27], and sick leave days [36]. From a clinical perspective, the findings of the present study suggest that delayed surgery for patients with ACL injury will cause damage to the medial meniscus, especially for patients who have greater anterior knee laxity and a higher pivot shift test grade.…”
Section: Discussionmentioning
confidence: 99%